2022
DOI: 10.1002/cncr.34178
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in frailty and geriatric assessment impairments in older adults with cancer in the Deep South: Results from the CARE Registry

Abstract: BACKGROUND: Despite recent advances in cancer, racial disparities in treatment outcomes persist, and their mechanisms are still not fully understood. The objective of this study was to examine racial differences in frailty and geriatric assessment impairments in an unselected cohort of older adults with newly diagnosed gastrointestinal (GI) malignancies. METHODS: This study used data from the Cancer and Aging Resilience Evaluation Registry, a prospective cohort study that enrolled older adults (≥60 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…To be clear, we accept that “race and ethnicity are social constructs, without scientific or biological meaning.” 8 It behooves all of us to reject these observed differences in frailty and functionality as inevitable or acceptable, to probe into their causes, and to work to provide equitable care to all patients with cancer. Williams and colleagues 2 make this stance strongly in their article when they allude to “racial disparities,” and we agree with them.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…To be clear, we accept that “race and ethnicity are social constructs, without scientific or biological meaning.” 8 It behooves all of us to reject these observed differences in frailty and functionality as inevitable or acceptable, to probe into their causes, and to work to provide equitable care to all patients with cancer. Williams and colleagues 2 make this stance strongly in their article when they allude to “racial disparities,” and we agree with them.…”
supporting
confidence: 53%
“…These investigators even comment on the possibility that their findings could reflect nothing more than self‐reporting differences among various groups of patients, but this possibility seems less likely to us, as the investigators used more than 1 patient‐reported instrument to generate their results and reach their conclusions. More importantly, Williams and colleagues 2 outline the need to probe into the role of systemic inflammatory markers, which could mechanistically drive frailty and compromised functionality and which might be reflective of longstanding stress, detrimental exposures, suboptimal lifestyle habits, and other environmental factors in a subpopulation of older patients with cancer 15 . These investigators suggest that such translational work is an important next step to better understand their observations, and we agree.…”
mentioning
confidence: 89%
See 3 more Smart Citations